Tumarkin-like phenomenon as a sign of therapeutic success in benign paroxysmal positional vertigo - Eliana T. Maranhão; Susan L. Whitney; Péricles Maranhão-Filho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: To describe an unusual patient reaction to maneuvers used in the treatment of posterior canal benign paroxysmal positional vertigo (PC-BPPV) that we termed the “Tumarkin-like phenomenon”. Methods: At a private practice, 221 outpatients were diagnosed and treated for PC-BPPV. The treatment consisted of performing the Epley or Semont maneuvers. At the end of these maneuvers, when assuming the sitting position, the patients’ reactions were recorded. Results: Thirty-three patients showed a Tumarkin-like phenomenon described by a self-reported sensation of suddenly being thrown to the ground. In the follow-up, this group of patients remained without PC-BPPV symptoms up to at least 72 hours after the maneuvers. Conclusion: The occurrence of a Tumarkin-like phenomenon at the end of Epley and Semont maneuvers for PC-BPPV may be linked with treatment success.